Implementation of Article 7 of Undang-Undang No. 1 of 1974 and Article 7 of Undang-Undang No. 16 of 2019 concerning the Minimum Age Limit for Marriage in Suppressing Cases of Early Marriage - Augusty, Arsista; Suyaman, Prahasti (Dinasti Research, 2025)
This study aims to examine the implementation of Article 7 of Undang-Undang No. 1 of 1974 and Article 7 of Undang-Undang No. 16 of 2019 concerning the minimum age of marriage in suppressing cases of early marriage, especially in the Sukabumi City area. Although there has been a change in the minimum age from 16 years to 19 years for women, the phenomenon of child marriage still continues to take advantage of the gap in marriage dispensation from the courts. Through an empirical juridical approach and supported by field data and interviews with judicial officials, this study shows that the high number of marriage dispensation applications after the change in the law indicates that the law is still weak in practice. Social, cultural, and lack of legal education are also the main causes of the high dispensation of child marriage. Therefore, a more progressive legal approach and the active participation of all parties are needed to strengthen child protection and suppress the practice of early marriage across the board.